Chokeberry Products and By-Products as the Potential Pharmaceuticals for Kidney Protection—An Experimental Study in Rats - Milica Milutinović; Nada Ćujić Nikolić; Tatjana Cvetković; Katarina Šavikin; Ivana Djordjević; Ljubinka Janković Veličković; Milica Randjelović; Bojana Miladinović; Suzana Branković; Dušanka Kitić (Plants)
The study aimed to investigate the protective effects of chokeberry fruit products and by-products against cisplatin-induced acute nephrotoxicity in rats. Potential mechanisms involving oxidative stress and inflammatory responses were examined through biochemical and histopathological analyses of kidney tissue. Chokeberry waste, along with the whole fruit extract and juice, was evaluated as a potential raw material for pharmaceutical use. The chemical composition of chokeberry juice and extracts was analyzed using spectrophotometry and HPLC. Rats were treated with chokeberry preparations via intragastric tube for ten days, with a single intraperitoneal dose of cisplatin (8 mg/kg BW) administered on the third day. Post-sacrifice, plasma samples were analyzed for biochemical nephrotoxicity markers, oxidative stress, and inflammatory markers. Kidneys were removed for histopathological and biochemical analysis. Cisplatin-induced acute nephrotoxicity was confirmed by elevated plasma creatinine and blood urea nitrogen levels. Additionally, lipid peroxidation was significantly elevated, while reduced glutathione and catalase activity were significantly reduced. Pro-inflammatory mediators IL-1β, TNF-α, and IL-6 levels were significantly increased in the cisplatin group. Treatment with chokeberry extracts and juice significantly mitigated these nephrotoxic effects, as confirmed by histopathological examination and biochemical marker analysis. Notably, the waste extract demonstrated greater efficacy than the whole fruit extract, likely due to its higher concentration of polyphenolic compounds, especially anthocyanins. These results highlight the potential of chokeberry as a therapeutic and preventive agent for kidney protection, emphasizing the value of by-products rich in biologically active compounds.